2(y-2)=y+7-2(-5y-2)

Simple and best practice solution for 2(y-2)=y+7-2(-5y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(y-2)=y+7-2(-5y-2) equation:



2(y-2)=y+7-2(-5y-2)
We move all terms to the left:
2(y-2)-(y+7-2(-5y-2))=0
We multiply parentheses
2y-(y+7-2(-5y-2))-4=0
We calculate terms in parentheses: -(y+7-2(-5y-2)), so:
y+7-2(-5y-2)
determiningTheFunctionDomain y-2(-5y-2)+7
We multiply parentheses
y+10y+4+7
We add all the numbers together, and all the variables
11y+11
Back to the equation:
-(11y+11)
We get rid of parentheses
2y-11y-11-4=0
We add all the numbers together, and all the variables
-9y-15=0
We move all terms containing y to the left, all other terms to the right
-9y=15
y=15/-9
y=-1+2/3

See similar equations:

| 4x+5x+6=3(4x-7)+9 | | 7x-7(-3x-20)=-84 | | 6(2x–5)+3=57x | | 32.5/5=x | | 12m–9m=9 | | (2)4x+2=4x+44 | | 3(γ+1)+2(γ-4)=2y-(γ-6) | | x2+10x+100=28-7x | | 14p-13p=15 | | 3x(x+2)(x-5)=0 | | 16(3p-5)=40+10(4p-8 | | 5(x+5)=6(x-6) | | 3(x-2)+4(x+3)=-8 | | 5/4=25n | | 11/7+1/6t=3 | | -6(5x-9)+7=-30x+61 | | 6(4x+2)=156 | | (5r-6)(2r+7)(r+5)=0 | | 4c-6=3c+6 | | (14/3)=2u | | 99x2-73x+10=0 | | 6x-1=3+6x | | X-9+6x=180 | | 3x+18=5x+28 | | 7=3w–2 | | 6(3x+2=66 | | 9m+8=72 | | 5b-2b=3 | | 88+5w=-22 | | 3(4x+7)=-14+11 | | z-6z=5z-2-z | | 4r-r=18 |

Equations solver categories